A gestão e o gerenciamento dos resíduos sólidos no município de São Luís-MA: os impactos gerados pela pandemia de Covid-19 nos Ecopontos - VILELA, Paulo Sérgio De Jesus (2023)
Copious research has shown that large-scale production resulting from the Industrial Revolution, made consumer goods more accessible to a greater number of people, however, with the greater production of goods, there was also an increase in the generation of solid waste and, for a long time, what was no longer serviceable was discarded inappropriately, giving rise to several dumps. Federal Law No. 12.305/2010 established the National Solid Waste Policy as a milestone in waste management in the country, stipulating guidelines for the proper disposal of waste and prohibiting environmentally harmful practices. However, despite the efforts, many municipalities still face challenges for environmentally sound management of solid waste, resulting in a problem that is difficult to solve. Thus, and starting from the understanding that municipal solid waste is a geographical, social, historical and spatially constructed object, and very pertinent to the perception of the relationship of man with space, we analyze through bibliographic research, investigate the management and management of MSW in the municipality of São Luís, in addition to the impacts caused by the Covid - 19 pandemic, which caused social isolation and completely changed the dynamics of world consumption. In this study, it discusses issues, political, social and environmental, regarding the management of MSR in the Ecopoints of São Luís and the impacts resulting from the Covid-19 pandemic, Configuring itself as a case study that has a descriptive character, in which an annexation was carried out between historical, bibliographic, documentary and exploratory research, having a qualitative-quantitative approach. In this way, primary data were used, collected during the field research phase, through semi-structured interviews, and secondary data, made available by public access databases. Thus, it was possible the structured elaboration of a framework of laws, maps and graphs that corroborate the reflections and conclusions of this research. The results show that even after more than ten years of the PNRS, the municipality of São Luís still faces several challenges to carry out a management and management of the MSU in an efficient way, and the Covid-19 pandemic has expanded the deficiencies, so that the waste pickers of recyclable materials are the most vulnerable and consequently those who have suffered the most the impact of a sector that suffers from problems of mismanagement, and that depends on political and personal interests in decision-making.